2005
DOI: 10.1002/ab.15555
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and commensalism in house mouse: a comparative study across Europe and the near east

Abstract: Species specific differences of house mouse social behavior compared to its closest relatives (aboriginal species Mus macedonicus, Mus spicilegus, and Mus spretus) have recently been suggested. However, substantial variation of behavioral traits between mouse populations has been also evidenced. Agonistic behavior of laboratory-born house mice from five commensal populations (Mus musculus musculus: central Czech Republic, Mus musculus domesticus: Bulgaria, Greece, Turkey, and natural Mus m. musculus/domesticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…This study is the extension of pilot experiments revealing conserved asymmetry in male aggressiveness between both strains representing M. m. musculus and M. m. domesticus [see also Pia´lek et al, 2008], that correspond to differences repeatedly reported from wild populations [Frynta et al, 2005;Thuesen, 1977;Van Zegeren and Van Oortmerssen, 1981;Volfova´et al, 2002], ancestral populations of the strains and populations along a transect across the Czech-Bavarian portion of the hybrid zone [Vosˇlajerova´and Pia´lek, unpublished data]. Even though the two subspecies and our model strains differ in many morphological and physiological parameters, we do not have any evidence and/or to our knowledge there is no study reporting subspecies-specific differences in hormonal levels or neurochemical differences that may lead to differences in aggressiveness.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This study is the extension of pilot experiments revealing conserved asymmetry in male aggressiveness between both strains representing M. m. musculus and M. m. domesticus [see also Pia´lek et al, 2008], that correspond to differences repeatedly reported from wild populations [Frynta et al, 2005;Thuesen, 1977;Van Zegeren and Van Oortmerssen, 1981;Volfova´et al, 2002], ancestral populations of the strains and populations along a transect across the Czech-Bavarian portion of the hybrid zone [Vosˇlajerova´and Pia´lek, unpublished data]. Even though the two subspecies and our model strains differ in many morphological and physiological parameters, we do not have any evidence and/or to our knowledge there is no study reporting subspecies-specific differences in hormonal levels or neurochemical differences that may lead to differences in aggressiveness.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have reported that two European subspecies of the house mouse, M. m. domesticus and M. m. musculus, differ markedly in levels of aggression, the former always winning dyadic encounters [Frynta et al, 2005;Pia´lek et al, 2008;Thuesen, 1977;Van Zegeren and Van Oortmerssen, 1981;Volfova´et al, 2002]. Unfortunately, most of the studies cited above are simple demonstrations of differences in aggression, with the exception of that by Volfova´et al [2002], who tested the idea that the differences in aggressiveness between these two subspecies are the result of genetic variation located on the Y chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…As males of most rodent species are more exploratory (Frynta 1994), possess larger home ranges (e.g. Brown 1969), exhibit more aggression (Čiháková and Frynta 1996;Frynta et al 2005) and consequently (Krackow 2005) are more migratory (Pocock et al 2005) than conspecific females, we can speculate that overproduction of males by Toxoplasma-infected females may considerably facilitate long-range transmission of the infection in natural situation.…”
Section: Discussionmentioning
confidence: 96%
“…One form is acute toxoplasmosis, which in immunocompetent subjects, spontaneously turns into the second form, i.e. Č iháková and Frynta, 1996 ;Frynta et al 2005) and consequently the more dispersing sex (e.g. The latter is clinically asymptomatic, life-long infection characterized by the presence of anti-Toxoplasma antibodies in the blood and Toxoplasma bradyzoites in tissue cysts.…”
Section: Introductionmentioning
confidence: 99%